UTILIZAREA STANDARDELOR OCUPAŢIONALE LA ELABORAREA PROGRAMELOR DE FORMARE PROFESIONALĂ CONTINUĂ - USM ADMIN (Moldova State University, 2008)
The vocational standards are a very important informational source for the development of permanent professional training. From the perspective of andragogical paradigm of motivation of learning, the vocational standards represent the futurological dimension of the longitudinal pattern of motivating the adults. According to this pattern, the training pro- grams, developed on the basis of vocational standards, stimulate the motivation of adults to learn. The article forwards some methodological suggestions with regard to the development of permanent professional training based on vocational standards.